2019
DOI: 10.3390/cells8121646
|View full text |Cite
|
Sign up to set email alerts
|

Copresentation of BMP-6 and RGD Ligands Enhances Cell Adhesion and BMP-Mediated Signaling

Abstract: We report on the covalent immobilization of bone morphogenetic protein 6 (BMP-6) and its co-presentation with integrin ligands on a nanopatterned platform to study cell adhesion and signaling responses which regulate the transdifferentiation of myoblasts into osteogenic cells. To immobilize BMP-6, the heterobifunctional linker MU-NHS is coupled to amine residues of the growth factor; this prevents its internalization while ensuring that its biological activity is maintained. Additionally, to allow cells to adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…This is in agreement with other studies that propose as well that the proximity of GF and integrins favors cell adhesion. [ 15,22,26 ] Moreover, cell adhesion on the samples functionalized with the RGD‐DWIVA peptide was effectively inhibited when C2C12 cells were preincubated with the potent integrin antagonist Cilengitide, [ 49 ] showing the synergistic enhancement in cell adhesion is specifically mediated by integrin binding to the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with other studies that propose as well that the proximity of GF and integrins favors cell adhesion. [ 15,22,26 ] Moreover, cell adhesion on the samples functionalized with the RGD‐DWIVA peptide was effectively inhibited when C2C12 cells were preincubated with the potent integrin antagonist Cilengitide, [ 49 ] showing the synergistic enhancement in cell adhesion is specifically mediated by integrin binding to the surface.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20,22,24,25 ] Recently, a specificity in integrin crosstalk with bound BMP‐2 has been shown by using surface nanopatterning of single BMPs homodimers copresented with integrin ligands. [ 26,27 ] While this approach shows that the nanoscale control over BMP‐2 distribution and the proximity of the GF with integrin binding sites favors cell adhesion and BMP‐mediated signaling, it is not possible with such system to control the stoichiometry of receptor binding sites, because the integrin ligands are sparsely distributed on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Other nano‐based strategies investigating the biological activity of immobilized BMP‐6 in concentrations down to 1 ng show enhanced duration of signaling and activity compared to soluble BMPs, making this an interesting approach for BSM. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Aspirates were subjected to density centrifugation followed by CD138‐purification using an AutoMACS Pro (Miltenyi, Bergisch Gladbach, Germany) as previously published. [ 9–33 ] For the experiments, negative fractions of plasma cell purification still containing malignant plasma cells alongside the mononuclear compartment of the bone marrow were used as previously described. [ 9 ] Cells were cultured in RPMI‐1640 medium supplemented with 10% fetal calf serum (FCS) and 2 ng mL −1 IL‐6.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies demonstrated that it is possible to directly trans-differentiate one adult cell type to the other using small molecules. Other studies investigated the underlying mechanisms [12][13][14]. These experiments, however, demonstrated that changes could only take place within cells from the same germ layer.…”
mentioning
confidence: 99%